2001
DOI: 10.1159/000047442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Water Rinse on ‘Labile’ Fluoride and Other Ions in Plaque and Saliva before and after Conventional and Experimental Fluoride Rinses

Abstract: Labile reservoirs are important in maintaining ion concentrations in oral fluids, especially after a fluoride dentifrice application, where a persistent increase in fluid fluoride can mitigate or reverse caries progression. In this study, the effect of experimental and conventional fluoride rinses on the in vitro and in vivo water–induced release of fluoride, calcium, phosphate, acetate and hydrogen ions from oral reservoirs was examined. At the start of each experiment, 13 subjects rinsed either with a conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
33
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 34 publications
9
33
1
Order By: Relevance
“…The sucrose rinse was administered 1 h after a fluoride rinse because this was considered to be the shortest postfluoride rinse time that could be anticipated before a subsequent cariogenic attack, and because previous studies suggested that, for a short period of time, plaque ions may be depleted by the water component of the fluoride rinse [Vogel et al, 2001]. The controlled-release experimental fluoride rinse, which uses the controlled release of fluoride from the hydrolysis of Na 2 SiF 6 in the presence of CaCl 2 to enhance the deposition of fluoride in oral tissue [Vogel et al, , 2001Chow et al, 2000], was chosen for these experiments for the following reasons: (1) in agreement with the studies described in the introduction, a preliminary experiment using similar experimental conditions found no effect on lactic acid production with an NaF rinse [Vogel, unpubl.…”
Section: Choice Of Experimental Conditions and Rinse Formulationmentioning
confidence: 99%
See 4 more Smart Citations
“…The sucrose rinse was administered 1 h after a fluoride rinse because this was considered to be the shortest postfluoride rinse time that could be anticipated before a subsequent cariogenic attack, and because previous studies suggested that, for a short period of time, plaque ions may be depleted by the water component of the fluoride rinse [Vogel et al, 2001]. The controlled-release experimental fluoride rinse, which uses the controlled release of fluoride from the hydrolysis of Na 2 SiF 6 in the presence of CaCl 2 to enhance the deposition of fluoride in oral tissue [Vogel et al, , 2001Chow et al, 2000], was chosen for these experiments for the following reasons: (1) in agreement with the studies described in the introduction, a preliminary experiment using similar experimental conditions found no effect on lactic acid production with an NaF rinse [Vogel, unpubl.…”
Section: Choice Of Experimental Conditions and Rinse Formulationmentioning
confidence: 99%
“…The controlled-release experimental fluoride rinse, which uses the controlled release of fluoride from the hydrolysis of Na 2 SiF 6 in the presence of CaCl 2 to enhance the deposition of fluoride in oral tissue [Vogel et al, , 2001Chow et al, 2000], was chosen for these experiments for the following reasons: (1) in agreement with the studies described in the introduction, a preliminary experiment using similar experimental conditions found no effect on lactic acid production with an NaF rinse [Vogel, unpubl. data], and (2) compared with an NaF rinse, the experimental rinse produced a much higher concentration of plaque and plaque fluid fluoride and a greater release of fluoride when plaque was acidified [Vogel et al, 1992[Vogel et al, , 2001, suggesting that a positive effect might be observed. More importantly, the plaque fluid concentration of ions other than fluoride has been shown to be very similar after either an NaF rinse or the experimental controlled-release rinse so that the results found here should be similar to those obtained with a conventional NaF rinse [Vogel et al, , 2001.…”
Section: Choice Of Experimental Conditions and Rinse Formulationmentioning
confidence: 99%
See 3 more Smart Citations